Elective transfer of one embryo is associated with a higher cumulative live birth rate and improved perinatal outcomes compared to the transfer of two embryos with in vitro fertilization - Rachel B. Mejia, D.O; Emily A. Capper, B.A; Karen M. Summers, M.P.H; Patrick Ten Eyck, Ph.D; Bradley J. Van Voorhis, M.D (Elsevier, 2021)
Objective: To compare the effects of initial elective single embryo transfer (ieSET) and initial double embryo transfer (iDET) strategies on the cumulative live birth rate (CLBR) and perinatal outcomes after IVF. Design: Retrospective cohort study. Setting: Society for Assisted Reproductive Technology (SART) reporting clinics. Patient(s): 49,333 patients with initial oocyte retrievals between January 2014 and December 2015. Intervention(s): None. Main Outcome Measure(s): The primary outcome was CLBR, defined as up to 1 live birth resulting from a retrieval cycle and linked transfer cycles. Secondary outcomes included cycles to pregnancy, multifetal delivery rate, infant birthweight, and perinatal mortality rate. Result(s): Compared to iDET, ieSET was associated with increased CLBR (74% vs. 57%; adjusted odds ratio [AOR], 1.32; 95% CI, 1.26-1.38). When stratified by age, the same trend was seen in all age categories, with statistical significance for those <38 years of age. ieSET was associated with reduced multifetal delivery (8% vs. 34%; AOR, 0.13; 95% CI, 0.12-0.14), increased birthweight (mean difference, 406 grams; 95% CI, 387-425), reduced preterm births (1.2% vs. 2.8%), and reduced perinatal mortality (0.5% vs. 1.2%). Compared with iDET, ieSET was associated with slightly more embryo transfer cycles (1.7 vs. 1.4 cycles; AOR, 1.19; 95% CI, 1.16-1.21) to achieve a pregnancy resulting in live birth. Conclusion(s): The association of ieSET with a higher CLBR and markedly improved perinatal outcomes outweigh the relatively minor increase in time to pregnancy, reinforcing the guidance for eSET in initial transfer cycles, particularly in younger patients with a good prognosis.